Dislocated Character Affirmation——A Case Study of Young Female Gamers' Identity in Online Games - Yang Xiaohong (Contemporary Social Sciences, 2017)
What are the real intentions of young women to play online games? Can they benefit more than just entertainment? Based on a 2-year followup survey of a young female online gamer, this paper explores the inner experiences of a young female gamers. Findings indicate that young female Chinese gamers attach importance to the choice of characters in the world of online games and that they establish a sense of identity in virtual space through character affirmation and interactions with other gamers. For young female gamers, who are eager to temporarily escape from reality, playing online games is a positive psychological compensation and a process for building self-confidence.